Analisis Kemampuan Pemecahan Masalah Siswa Pada Materi Aritmatika Sosial - Herika Herika; Belia Andara; Filia Anggriani (JEID: Journal of Educational Integration and Development, 2022)
This research is a quantitative descriptive study that aims to analyze students' problem solving skills through problem solving ability test instruments and interviews at SMA Negeri 8 Pontianak students. Students are selected based on class rankings which are then classified into three categories, there are 2 top-ranking students, 2 middle-ranking students, and 2 lower-ranking students. The score is seen from the indicator table according to Poyla. The data collection technique is by giving test questions in the form of essays to students and interviews with students at random, then analyzed according to the indicator table. The results obtained indicate that the problem solving ability of students is still low.